2010
DOI: 10.1123/jab.26.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Full Body Inertial Measurement System in Alpine Skiing: A Comparison with an Optical Video Based System

Abstract: This study aims at determining the accuracy of a full body inertial measurement system in a real skiing environment in comparison with an optical video based system. Recent studies have shown the use of inertial measurement systems for the determination of kinematical parameters in alpine skiing. However, a quantitative validation of a full body inertial measurement system for the application in alpine skiing is so far not available. For the purpose of this study, a skier performed a test-run equipped with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 7 publications
1
61
0
1
Order By: Relevance
“…In order to analyze technique of the throw, that is kinematic parameters of the basketball jump shot, we used the MVN inertial suit MVN Biomech Pro-Inertial motion capture (Xsense, Enschede, The Netherlands). Previous studies have showed that this kind of equipment is appropriate for the analysis of sports movements when it comes to short physical actions, such as the jump shot (Krüger & Edelmann-Nusser, 2010;Supej, 2010;2011). The moment when the ball is released from the hand cannot be determined by the MVN program, so we also used a Casio Exilim -F1 camera that takes up to 300 photos per second.…”
Section: Methodsmentioning
confidence: 99%
“…In order to analyze technique of the throw, that is kinematic parameters of the basketball jump shot, we used the MVN inertial suit MVN Biomech Pro-Inertial motion capture (Xsense, Enschede, The Netherlands). Previous studies have showed that this kind of equipment is appropriate for the analysis of sports movements when it comes to short physical actions, such as the jump shot (Krüger & Edelmann-Nusser, 2010;Supej, 2010;2011). The moment when the ball is released from the hand cannot be determined by the MVN program, so we also used a Casio Exilim -F1 camera that takes up to 300 photos per second.…”
Section: Methodsmentioning
confidence: 99%
“…To measure kinematic variables we used Xsens MVN inertial suit system with 17 three dimensional accelerometers /gyroscopes/ magnetometers placed on each foot, calf, thigh, hand, forearm, upper arm, shoulder, sternum, lower back and head. Xsens MVN system showed high validity and reliability in previous research (Brennan et al, 2011;Krüger and Edelmann-Nusser, 2010;Zhang, 2013) with error of up to 3 degrees for all axis. Result of shot put was measured according to IAAF rules (http://www.iaaf.org/about-iaaf/documents/rulesregulations/ IAAF Competition Rules 2016-2017 in force from 1 November 2015.pdf).…”
Section: Methodsmentioning
confidence: 55%
“…More details about the GNSS system can be found in [ 14 ]. The GNSS measurement setup was combined with an IMU motion capture suit (Xsens MVN , Xsens Technologies, Enschede, The Netherlands) for capturing the full-body skier's posture as in previous studies [ 4 , 15 ]. The IMU motion capture suit (MVN) had 17 motion-tracking sensors.…”
Section: Methodsmentioning
confidence: 99%